Basic energy statistics and energy balances for Nigeria 1970-1983 - Nigerian National Petroleum Corporation (Lagos : Economic Research & Intelligence Dept., Nigerian National Petroleum Corporation, 1984)
This handbook is sets out to identify the various sources of energy components and their distribution net-work through out the various sectors of the Nigerian economy. the work has been divided into three main areas: 1- the basic data in its original units, 2- energy balance using a common unit of measure, and 3- energy balances being dis-aggregated into further components.
aia 06/03/2019, nmn 13/03/19
Loans
Keywords: Energy industries; Energy statistics; Energy policy; Nigeria